2016
DOI: 10.1159/000446657
|View full text |Cite
|
Sign up to set email alerts
|

Association of a <b><i>PARK2</i></b> Germline Variant and Epithelial Ovarian Cancer in a Southern Brazilian Population

Abstract: Ovarian cancer (OC) is the eighth most common cancer among women in Brazil and seventh in the world population. OC has a high mortality rate and is difficult to diagnose. Currently, OC detection most often occurs at an advanced stage of the disease due to its silent progression, which contributes to the high mortality rate. Available genetic markers are not considered specifically enough for an initial and definite diagnosis. The association with new genes involved with OC can provide a better understanding of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…To date, evidence indicated that PRKN is a tumor suppressor. As reported, downregulation of PRKN had been associated with ovarian, colorectal, and cervical cancers (Song et al, 2013;Klimczak et al, 2016;Bhat et al, 2019). CCAAT/enhancer binding protein beta (CEBPB), as a family of transcription factors of the basic leucine zipper (bZIP) class, is bound to DNA as homodimers and heterodimers.…”
Section: Discussionmentioning
confidence: 95%
“…To date, evidence indicated that PRKN is a tumor suppressor. As reported, downregulation of PRKN had been associated with ovarian, colorectal, and cervical cancers (Song et al, 2013;Klimczak et al, 2016;Bhat et al, 2019). CCAAT/enhancer binding protein beta (CEBPB), as a family of transcription factors of the basic leucine zipper (bZIP) class, is bound to DNA as homodimers and heterodimers.…”
Section: Discussionmentioning
confidence: 95%